2015
DOI: 10.1097/jsm.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Stress Fracture of the Supracondylar Process of the Humerus in a Professional Tennis Player

Abstract: The supracondylar process of the humerus is an anatomic variant present in 1% of the population associated with a fibrous band, the ligament of Struthers that attaches it to the medial epicondyle, and may serve as a proximal origin of a fascicle of the pronator teres. Fractures of the supracondylar process of the humerus are extremely rare. To the best of our knowledge, this is the first report of a stress fracture of the supracondylar process. We present the case of a professional tennis player with a stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…This pathogenic entity is known as the supracondylar process syndrome [31]. Clinically, symptoms such as radiating or acute pain, complaints of sensory disturbances and reports of decreased grip strength are common in pathological cases [19,31,32]. During physical examination, vascular disturbances, sensory deficits, and decreased muscle strength, related to regions and structures innervated by the median nerve, can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathogenic entity is known as the supracondylar process syndrome [31]. Clinically, symptoms such as radiating or acute pain, complaints of sensory disturbances and reports of decreased grip strength are common in pathological cases [19,31,32]. During physical examination, vascular disturbances, sensory deficits, and decreased muscle strength, related to regions and structures innervated by the median nerve, can be observed.…”
Section: Discussionmentioning
confidence: 99%
“…The signs and symptoms will develop in accordance with the different variations of the regional anatomy, considering the anatomical characteristics of the supracondylar process, the course and thickness of the ligament, when present, and how soft structures pass through these elements. Diagnosis relies on physical examination and imaging tests, including oblique view radiographs of the forearm, computed tomography, and magnetic resonance imaging [32,33]. Electroneuromyography can be used to assess the severity of neurovascular compression [29].…”
Section: Discussionmentioning
confidence: 99%
“…Fracture of the bone spur or concomitant compression of the ulnar nerve has been also described as a rare cause of pain in the presence of supracondylar process [ 3 ]. Pedret et al reported a case of a professional tennis player suffering from non-traumatic anteromedial arm pain and elbow stiffness [ 10 ]. The symptoms were attributed to stress fracture of the supracondylar humeral process after excessive traction of the pronator teres and the diagnosis was confirmed with x-rays and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Pedret et al 25 apresentaram o caso de um tenista profissional, com fratura por estresse do processo supracondilar do úmero, que passou por cirurgia para evitar possíveis deslocamentos e complicações neurovasculares. Informam ser este o primeiro relato de uma fratura por estresse do processo supracondilar, acreditam que a tração excessiva do pronador redondo tenha sido o causador da fratura que foi visualizada tanto no exame radiográfico como na ressonância magnética.…”
Section: Discussionunclassified